Peluang Pendidikan Islam : Kajian Perspektif Filsafat Ilmu - Mohammad Bagus Mansur; Akhmad Ansori; Nia Novita Sari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study discusses the opportunities for the development of Islamic education from the perspective of solutions offered by the philosophy of science in the era of technological advancement. Islamic educational institutions are confronted with complex problems that cannot always be resolved independently. The philosophy of science offers several solutions on how to address the challenges commonly faced by educational institutions. Often, educational institutions focus excessively on analyzing the challenges or problems they encounter, whereas there are other aspects that can be utilized as supporting factors for the development of Islamic education, namely by examining existing opportunities and implementing them effectively. This research employs a literature review method with a qualitative approach, complemented by case study analysis across various educational institutions. Many Islamic educational institutions, both formal and non-formal, have utilized opportunities as a primary strategy for developing Islamic education. Various solutions are proposed, including curriculum integration, strengthening institutional organizational structures, improving human resources as well as facilities and infrastructure, and presenting innovative ideas implemented by institutions in developing Islamic education.